The Effects of Hyperbaric Oxygen Treatment on Total Antioxidant Capacity and Prolidase Activity after Bile Duct Ligation in Rats. (2nd November 2017) - Terzioglu, Duygu; Uslu, Lebriz; Simsek, Gonul; Atukeren, Pinar; Erman, Hayriye; Gelisgen, Remise; Ayvaz, Suleyman; Aksu, Burhan; Uzun, Hafize
ABSTRACT: Background : Hyperbaric oxygen (HBO) therapy may improve cholestasis, increase hepatic regeneration, and decrease oxidative stress in liver. In this study, we aimed to investigate the effects of HBO therapy on hepatic oxidative stress parameters, such as total thiol groups (T-SH), protein carbonyl (PCO), and total antioxidant capacity (TAC) as well as the predictive value of the noninvasive biochemical marker, sialic acid (SA), and prolidase activity in bile duct ligation (BDL)-induced oxidative damage and fibrosis in rats. Methods : We divided 32 adult male Sprague Dawley rats into four groups: sham, sham + HBO, BDL, and BDL + HBO; each group contained eight animals. We placed the sham + HBO and BDL + HBO groups in an experimental hyperbaric chamber, in which we administered pure oxygen at 2.5 atmospheres for 90 min on 14 consecutive days. Results : The application of BDL significantly increased PCO levels and prolidase activity, and decreased T-SH and TAC levels. HBO significantly decreased PCO levels and prolidase activity and increased T-SH and TAC levels in the liver tissues. There was no significant difference in sialic acid levels between any groups. Conclusions : These results indicate that HBO therapy has hepatoprotective effects on BDL-induced injury by decreasing PCO and prolidase activity and increasing antioxidant activities. We therefore suggest that HBO therapy may be useful after BDL-induced injury.